Analisis Faktor-Faktor Yang Mempengaruhi Pengungkapan Sustainability Report Pada Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia - Sari Mujiani; Tuti Nurfitri (AKRUAL : Jurnal Akuntansi dan Keuangan, 2020)
Sustainability report is a voluntary report to present corporate responsibility on social, economy, and environment aspects. This report is a part of corporate disclosures to obtain stakeholder’s legitimacy. Stakeholder and obtaining legitimacy from public as the implementation of good corporate governance. This study aims to find empirical evidence about the effect of liquidity, company activity, managerial ownership on the disclosure of the company’s sustainability report LQ45 listed on the Stock Exchange 2011-2016. The number of companies sampled in this study as many as 9 companies. This study is based on a purposive sampling method. Testing the hypothesis in this study using multiple regression analysis using SPSS 21. The result showed that the liquidity, company activity significantly influence sustainability disclosure report. Meandwhile, managerial ownership does not significantly influence sustainability disclosure report